2018
DOI: 10.1111/ctr.13429
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of interferon type I pathway‐related genes RSAD2 and ETV7 specifically indicates antibody‐mediated rejection after kidney transplantation

Abstract: Context Antibody‐mediated rejection (ABMR) after kidney transplantation (KTx) remains the crucial obstacle to successful long‐term graft function. The identification of gene signatures involved in ABMR could grant the basis for better prevention and treatment strategies. Objective The identification of gene signatures in whole blood cells specific for ABMR after KTx. Materials and methods Total RNA from blood cells of 16 kidney‐transplanted patients with ABMR, stable graft function (SGF), and with T‐cell‐media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…In particular, we chose to use IFN-β as type I IFN, given the previous data in literature suggesting a negative role for IFN-β in breast cancer stemness [ 56 , 57 ], and IFN-γ as type II IFN, being the only member of this subfamily. Since, as mentioned above, ETV7 itself is a well-recognized Interferon-stimulated gene (ISG) [ 26 , 28 ], we first analyzed its expression in response to IFN-β and IFN-γ in MCF7 cells. As expected, we observed a robust and significant induction of ETV7 expression in response to both types of IFNs, with a peak of induction at 8 h for IFN-β and 24 h for IFN-γ, confirming that ETV7 is strongly responsive to IFNs also in the breast cancer-derived MCF7 cell line (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we chose to use IFN-β as type I IFN, given the previous data in literature suggesting a negative role for IFN-β in breast cancer stemness [ 56 , 57 ], and IFN-γ as type II IFN, being the only member of this subfamily. Since, as mentioned above, ETV7 itself is a well-recognized Interferon-stimulated gene (ISG) [ 26 , 28 ], we first analyzed its expression in response to IFN-β and IFN-γ in MCF7 cells. As expected, we observed a robust and significant induction of ETV7 expression in response to both types of IFNs, with a peak of induction at 8 h for IFN-β and 24 h for IFN-γ, confirming that ETV7 is strongly responsive to IFNs also in the breast cancer-derived MCF7 cell line (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, ETV7 over-expression in human U937 cells was shown to impede monocytic differentiation [ 25 ]. ETV7 is also recognized as an Interferon (IFN)-stimulated gene (ISG), as its expression was shown to be induced by type I, type II, and type III IFN treatment in different cell types [ 26 28 ]. Elevated ETV7 expression has been associated with several tumor types; however, the role of ETV7 in cancer has been poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have been more commonly performed on renal biopsy samples as they provide sufficient material for RNA extraction. As listed in Table 1, gene signatures associated with fibrosis, i-IFTA, chronic rejection (ABMR and TCMR) and graft failure can be identified by determining gene expression profiling (45)(46)(47)(48)(49)(50)(51)(52)(53). Importantly, the gene set has higher predictive capacity than that of baseline clinical variables, and clinical and pathological variables.…”
Section: Transcriptomic Biomarkersmentioning
confidence: 99%
“…In addition, genome-wide transcriptional profiling has demonstrated that the combined treatment of MCF7 breast cancer-derived cells with the chemotherapeutic agent doxorubicin and the inflammatory cytokine TNF-α results in the synergistic induction of ETV7 (21). ETV7 was also identified as an interferon (IFN)-stimulated gene (ISG), and its expression is known to be up-regulated upon the treatment with type I, type II, and type III interferons (22)(23)(24)(25). We have recently shown that ETV7 negatively regulates the type I interferon response, and it is known to be involved in the viral immune response by suppressing a subset of ISGs that are important for the control of influenza and SARS-CoV-2 viruses (26,27).…”
Section: Introductionmentioning
confidence: 99%